(-2+m)-(-2m-3)=-8
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 19:23:37
(-2+m)-(-2m-3)=-8(-2+m)-(-2m-3)=-8(-2+m)-(-2m-3)=-8由原方程得:-2+m+2m+3=-83m+1=-83m=-9m=-3m=7/3(-2+m)-(-2
(-2+m)-(-2m-3)=-8
(-2+m)-(-2m-3)=-8
(-2+m)-(-2m-3)=-8
由原方程得:-2+m+2m+3=-8
3m+1=-8
3m=-9
m=-3
m=7/3
(-2+m)-(-2m-3)=-8
-2+m+2m+3=-8
3m+1=-8
3m=-9
m=-3
计算:(m+3m+5m+…+2015m)-(2m+4m+6m+…+2014m)=
{[(1.5m+1.8m)×2+(4.5m×2m)]×(3.6m-0.15m)-0.8m×2m-1.5m×0.5m-1.0m×0.5m}×4间×3层+[(4.827m×2+2.4m×2m)×(3.6m-0.15m)-1.0m×2.1m×2面-1.0m×2.1m-1.2m×0.6m-1.2m×1.8m]×2层 +(6.387m+4.435m+6m+2.247m+2.247m×2+1.2m×2+3m×2)×(3.6m-0.15m)-1.2
(m-2)(m²+2m+4)-2m(m²-3),其中m=2
m/n=5/3,求(m/m+n)+(m/m+n)-(n^2/m^2-n^2)
化简:(2m/m+2-m/m-2)/ ( m/m²—4)=?
已知m/n=5、,求(m/(m+n))+(m/(m-n))-(n^2/(m^3-n^2))
计算:(2m*7m*3m)/(-42)m.(m为正整数)m是次方
(m²-2m+1/m²-1+m²-m/m)÷(1+m/2,其中m=-3)
计算:(m+3m+5m+…+2009m)-(2m+4m+6m+…+2008m)=_______
(m+3m+5m+...+2015m)-(2m+4m+6m+...+2014m)=
m-2m-3m+4m-5m-6m+7m.2004m=?
(m+3m+5m.+2013m)-(2m+4m+6m+.+2012m)=?
化简求值 m-4/m^2-9(1加上 14m-7/m^2+8m+16)÷1/m-3 其中m=5化简求值:(m-4)/(m^2-9)•{1+[(14m-7)/(m^2+8m+16)]}÷[1/(m-3) ]其中m=5
已知,m^2+8m-1=0,求代数式(1-m)(1+m)+(m-2)^2-2(m+3)^2的值
已知:m^2+8m-1=0.求(1-m)(1+m)+(m-2)^2-2(m+3)^2的值 ,有过程,谢谢!
已知m²+8m-1=0,求代数式(1-m)(1+m)+(m-2)²-2(m+3)²的值
6√(3-4m)-3㎡√(3-4m)-8m√(3-4m)-9m+12㎡+2m^3=0
8m²-5m(-m+3n)+4m(-4m-2分之5n)其中m=2n=1